2005
DOI: 10.1016/j.ijgo.2005.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Ominous cervical cytopathology in women with lupus

Abstract: Recent studies have demonstrated cervical cancer as among the most common malignancies in lupus [1]. Hence, screening for pre-cancerous lesions of the cervix is vital for these patients. Previous studies by our group and others [1][2][3][4] have demonstrated an increased frequency of cervical dysplasia in women with lupus. Data on the effect of immunosuppressive therapy suggest a correlation with abnormal pap smears, [4] as well. To extend the results of our previous study to assess the risk for cervical dyspl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Methodology used for review After the search for articles was made, the authors independently evaluated whether the articles analyzed could be included in the review. The full articles were assessed, with the exception of five studies that were in abstract form from international meetings [14][15][16][17][18]. The following data were extracted: study design, sample size, number of controls, diagnostic criteria, measures of frequency of HPV infection, cervical neoplasia, cervical cancer, and the association with immunosuppressive drugs.…”
Section: Methodsmentioning
confidence: 99%
“…Methodology used for review After the search for articles was made, the authors independently evaluated whether the articles analyzed could be included in the review. The full articles were assessed, with the exception of five studies that were in abstract form from international meetings [14][15][16][17][18]. The following data were extracted: study design, sample size, number of controls, diagnostic criteria, measures of frequency of HPV infection, cervical neoplasia, cervical cancer, and the association with immunosuppressive drugs.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that women with SLE were found to have an increased frequency of abnormal cervical Papanicolaou (Pap) smears compared with the general population [21]. A cohort analysis of lupus patients in the Wayne State University Lupus Registry indicated that women with lupus were 3.5-times more likely to develop high-grade cervical dysplasia or cervical cancer than the controls [22]. Published data have not emphasized an increase in invasive cervical cancers in SLE, compared with the general population [23], but it is not a common malignancy and single-center studies often cannot represent the risk of malignancy with precision.…”
Section: Cervical Cancer and Dysplasiamentioning
confidence: 99%
“…A cohort analysis of lupus patients in the Wayne State University Lupus Registry indicated that women with lupus were 3.5-times more likely to develop high-grade cervical dysplasia or cervical cancer than the controls [22]. Published data have not emphasized an increase in invasive cervical cancers in SLE, compared with the general population [23], but it is not a common malignancy and single-center studies often cannot represent the risk of malignancy with precision.…”
Section: Hematologic Cancersmentioning
confidence: 99%